STUDENTS’ REFLECTIONS ON WEEKLY VLOGGING IN A SPEAKING FOR ACADEMIC PURPOSES COURSE: CHALLENGES AND PEDAGOGICAL IMPLICATIONS - Priajana, Nana; Hidayat, Hendi; Basir, Amin (IJEE (Indonesian Journal of English Education), 2025)
Adding vlogging to academic speaking classes could be both new and hard at a time when digital expression is becoming more and more important in how we learn and talk to each other. This study investigates how students in a Speaking for Academic Purposes class at UIN Siber Syekh Nurjati Cirebon reflected on making vlogs as their tasks. It talks about the problems they had and what learning through vlogs means for teaching. We applied an explanatory sequential mixed methods design to collect data from 46 third-semester ELT students. We collected data through a structured questionnaire and in-depth interviews with three students who were at different levels of performance. The numbers showed that using language, feeling bad, and having technical problems were all moderately to very hard. Students said they got a lot out of it, like more confidence, better speaking skills for school, and more interest in school. Qualitative data confirmed these findings, showing that students had more freedom, motivation, and self-awareness. The study finds that, even though there were some problems, weekly vlogging is a fun and useful way to improve academic speaking in digital learning settings.